1992
DOI: 10.1002/atr.5670260106
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in traffic‐related mortality and morbidity among pedestrians in Quebec, 1983‐1988

Abstract: In this study we analyze thedmographic and geographical distribution ofpedestrian accidents (n=28,452) in the QuebecMunicipalitD rkgionales de comt6 (MRC) reported between January 1, 1983 and December 31, 1988. In order to be able to make comparisons between MRCs. we have created in Comparative Mortality Index and a Comparative Morbidity Index. We use a logistic regression model to single out explanatoxy factors. The main tendencies which are apparent in the demographic analysis are an overrepresentation of yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
3
0
3
Order By: Relevance
“…Joly et al (1988) noted that men's mortality rate is one and a half times higher than women's and that non-severe injuries are greater in men than women. Leaf and Preusser (1999) noted that male pedestrians are over-represented in injuries: among 21,751 injury cases studied, 70.2 % involved males and only 29.8 % involved females.…”
Section: Introductionmentioning
confidence: 99%
“…Joly et al (1988) noted that men's mortality rate is one and a half times higher than women's and that non-severe injuries are greater in men than women. Leaf and Preusser (1999) noted that male pedestrians are over-represented in injuries: among 21,751 injury cases studied, 70.2 % involved males and only 29.8 % involved females.…”
Section: Introductionmentioning
confidence: 99%
“…Saúde Colet., 2020;28(2):165-179 177/179177 Análisis espacial de mortalidad El riesgo de mortalidad en automovilistas y ciclistas se incrementó en áreas de baja densidad poblacional. Ambos resultados coinciden con lo estudiado en países desarrollados, registrando una relación negativa entre la mortalidad por lesiones de tránsito y la densidad poblacional 5,7,31,32 . Otros estudios han analizado los factores que contribuyen a mayores niveles de mortalidad en áreas de baja densidad poblacional, considerando de manera agregada a todas las víctimas fatales por lesiones de tránsito o sólo los ocupantes de vehículos de motor.…”
Section: Discussionunclassified
“…Fueron analizados los datos de mortalidad por lesiones de tránsito, de acuerdo a los códigos de la Clasificación Internacional de Enfermedades, Décima Revisión (CIE-10). Se consideraron los siguientes usuarios de vías de tránsito (cuarto código entre corchetes): peatones (V01-06 [1] y V09 [2][3]); ciclistas (V10-V18 [3][4][5]9] y V19 [4][5][6]9]); ocupantes de motocicletas (V20-28 [3][4][5]9] y V29 [4][5][6]9]); ocupantes de automóviles (V40-48 [4][5][6][7]9] y V49 [4][5][6]9]); y usuarios no especificados (V87 [0-9] y V89 [2][3]9]). Se seleccionaron estos usuarios de vías de tránsito ya que constituyen los casos de mortalidad por lesiones de tránsito más frecuentes en Argentina.…”
Section: Métodounclassified
See 1 more Smart Citation
“…Other studies reported a greater propensity for males to cross on red pedestrian lights (Rosenbloom, 2009; Tom & Granié, 2011). Traffic-related mortality is also higher among male than female pedestrians (Joly et al, 1992). Male cyclists were more likely than females to cross a railway track when it was dangerous to do so, that is, before the end of warning signals after a train had recently passed (Cobey et al, 2013).…”
mentioning
confidence: 99%